Bidirectional association between handgrip strength and ADLs disability: a prospective cohort study - Dai, Senjie; Wang, Shihui; Jiang, Siya; Wang, Dongying; Dai, Chenglong (Frontiers in Public Health, 2023)
Background Decreased handgrip strength (HGS) and activities of daily living (ADL) disability are common in aging populations. No studies have evaluated the bidirectional associations between HGS and ADL disability. This study aimed to explore the bidirectional effects of HGS and ADL disability. Methods This study analyzed data from two waves (2011 and 2015) of China Health and Retirement Longitudinal Study (CHARLS). Low HGS is defined by the Asian Working Group for Sarcopenia criteria. Meanwhile, disability was assessed by ADLs scale. The prospective bidirectional association between HGS and ADL disability was examined using binary logistic regression. Subgroup analysis were performed according to age and gender. Results A total of 4,902 and 5,243 participants were included in the Stage I and Stage II analyses, respectively. On the one hand, low HGS was significantly associated with subsequent ADL disability. The odds ratio (OR) value of developing BADL disability and IADL disability were 1.60 (95% confidence interval (CI): 1.23–2.08) and 1.40 (95% CI: 1.15–1.70), respectively, in participants with low HGS. On the other hand, baseline ADL disability was associated with an increased risk of developing low HGS. The OR value of developing low HGS were 1.84 (95% CI: 1.34–2.51) and 1.46 (95% CI: 1.19–1.79) for participants with BADL disability and participants with IADL disability, respectively. Lastly, the strength of the bidirectional associations varied among subgroups. Conclusions A significant bidirectional associations were identified between HGS and ADL disability. Interventions should be developed to prevent the development or progression of both low HGS and ADL disability.